Analisis Pengaruh Kesehatan dan Keselamatan Kerja terhadap Produktivitas Karyawan di PT Mitra Indah Lestari - Risha Maisaroh; Ummi Nadroh (MASALIQ, 2025)
The high rate of workplace accidents in Indonesia indicates that the implementation of occupational health and safety remains a strategic issue in maintaining employee productivity. Although several previous studies have examined the relationship between workplace safety and productivity, the findings have been inconsistent. This study aims to analyze the impact of occupational health and safety implementation on employee productivity at PT Mitra Indah Lestari. A qualitative method with a case study approach was employed. Data were collected through interviews, direct field observations, and a review of relevant literature. The findings demonstrate that a systematically designed occupational health and safety system contributes to creating a safe, comfortable, and supportive work environment that enhances employee well-being. These results indicate that workplace safety functions not only as a preventive measure against accident risks but also as a management strategy to improve human resource effectiveness and promote task flexibility. This study offers practical contributions to corporate policy development by supporting the creation of an integrated safety system aligned with productivity enhancement efforts.